VARIETY OF THE JAVANESE LEXICON “SLEEPING” IN JOMBANG: STUDY OF GEOGRAPHIC DIALECTOLOGY - Khoirunnisa, Krismonika; Ziqriyani, Dede Putri (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
This research article describes the variation of the Javanese lexicon "sleeping" and its distribution in the Jombang area, East Java. The objectives of this study were to classify the variation of the "sleeping" lexicon in the Jombang area and design the variation of "sleeping" lexicon according to the distribution. This type of research is a qualitative descriptive study using the method of leading proficiency, namely conducting interviews with speakers without directly meeting the speakers (interview via WhatsApp as the media). It used techniques record as support and tools for mapping and classifying data. This study's data was collected at two points: the Kaliwungu village (Jombang City) and Banjardowo village (District of Jombang) as target investigators to conduct the interview. This study used the dialectology theory as a basis for analyzing the data obtained. The results show that the Javanese language variation of "Sleeping" has many different linguals, meanings, and forms even though they are in the same area (Jombang).